Zoo-Integrations: On Beasts of Burden by Sunaura Taylor - Jarzyna, Anita (Porównania, 2022)
This article is a contextual discussion of Sunaura Taylor’s pioneering book Beasts of Burden: Animal and Disability Liberation, dedicated to a parallel critique of anthropocentrism and ableism as two interlocking systems of oppression that propel each other. The review notes the prospects for a (critical) use of the American scholar’s thesis in literary studies, and points out examples of specific works deserving reinterpretation within such a framework.